Efficacy and limitations of low-cost adsorbents for in-situ stabilisation of contaminated marine sediment. (1st March 2019) - Wang, Lei; Chen, Season S.; Sun, Yuqing; Tsang, Daniel C.W.; Yip, Alex C.K.; Ding, Shiming; Hou, Deyi; Baek, Kitae; Ok, Yong Sik
Abstract: Recycling waste materials as adsorbents for stabilising contaminated marine sediment is a low-cost and sustainable remediation method. The objective of this research was to evaluate the efficacy of organic (lignite and green waste compost) and inorganic wastes (acid mine drainage sludge (AMDS) and coal fly ash (CFA)) on metal stabilisation and assess the leachability of minerals from the adsorbents. The kinetic results illustrated that Zn (0.21 mg L −1 ) and Cu (0.16 mg L −1 ) quickly released from the sediment within 30 min. The continuous column leaching tests showed that the addition of carbonaceous lignite effectively reduced leaching of Zn (4.5–7.0 mg L −1 ) and Pb (0.05–0.06 mg L −1 ) after 100 pore volumes, although the stabilisation capacity was lower than that of activated carbon. In comparison, two inorganic industrial by-products (AMDS and CFA) outcompeted the stabilisation performance of organic materials, which reduced the long-term leaching concentrations of Cu and Zn to below 1 mg L −1 . The AMDS even provided comparable efficiency to the commercial zero-valent iron due to its abundant sorption sites and alkaline earth metals for contaminant adsorption and precipitation. However, the addition of waste adsorbents resulted in elevated leaching of Mn, Fe, and Al from the lignite- and AMDS-amended sediment, which may pose toxic risks to benthic organisms. the proposed waste adsorbents present a low-cost and low-carbon treatment for in-situ contaminated sediment remediation. Graphical abstract: Highlights: Toxic elements were rapidly released from contaminated marine sediment. Inorganic by-products outcompeted organic materials for efficient stabilisation. AMDS and ZVI were the most effective amendments for sediment remediation. Elevated leaching of Mn and Fe from low-cost amendments need further assessment.